2014
DOI: 10.1155/2014/790851
|View full text |Cite
|
Sign up to set email alerts
|

Flavocoxid, a Nutraceutical Approach to Blunt Inflammatory Conditions

Abstract: Flavonoids, from Scutellaria baicalensis (Chinese skullcap) and Acacia catechu (black catechu), have been shown to exert a variety of therapeutic effects, including anti-inflammatory, antiviral, antibacterial, and anticancer activities. Flavocoxid is a mixed extract containing baicalin and catechin and it acts as a dual balanced inhibitor of cyclooxygenase-1 (COX-1) and COX-2 peroxidase enzyme activities with a significant inhibition of 5-lipoxygenase (5-LOX) enzyme activity in vitro. Flavocoxid downregulates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 43 publications
(70 reference statements)
1
22
0
Order By: Relevance
“…Flavocoxid is a botanically based blend composed of purified baicalin from Scutellaria baicalensis and catechin from Acacia catechu . Since 2004, it is marketed as Limbrel by Primus Pharmaceuticals (Scottsdale, AZ, USA) and it is classified as a prescription medical food by FDA for the clinical dietary management of osteoarthritis . The mechanism of action of flavocoxid includes the inhibition of COX and LOX branches of AA cascade, antioxidant actions, and the downregulation of inducible inflammatory pathways.…”
Section: Identification Of Novel Targets In the Arachidonic Acid Cascadementioning
confidence: 99%
“…Flavocoxid is a botanically based blend composed of purified baicalin from Scutellaria baicalensis and catechin from Acacia catechu . Since 2004, it is marketed as Limbrel by Primus Pharmaceuticals (Scottsdale, AZ, USA) and it is classified as a prescription medical food by FDA for the clinical dietary management of osteoarthritis . The mechanism of action of flavocoxid includes the inhibition of COX and LOX branches of AA cascade, antioxidant actions, and the downregulation of inducible inflammatory pathways.…”
Section: Identification Of Novel Targets In the Arachidonic Acid Cascadementioning
confidence: 99%
“…Some studies reported that baicalin directly reduced arachidonic acid metabolism via inhibition of phospholipase A2 (PLA2), COX and 5-lipoxygenase (5-LOX), leading to a decrease in the production of leukotrienes (LTs), thromboxanes (TXB), and prostaglandins (PGs) as well as the infiltration of inflammatory cells and MPO release in chronic inflammatory response [11,[30][31][32][33]. Furthermore, baicalin inhibited the pro-inflammatory gene expression via down-regulating the TLRs/NF-κB signaling, such as COX-2, iNOS, TNF-α , IL-6, IL-13 and HMBG-1 in cervical tissue and colon tissue [11,30,32].…”
Section: The Pharmacological Effects Of Baicalinmentioning
confidence: 99%
“…Some studies reported that baicalin directly reduced arachidonic acid metabolism via inhibition of phospholipase A2 (PLA2), COX and 5-lipoxygenase (5-LOX), leading to a decrease in the production of leukotrienes (LTs), thromboxanes (TXB), and prostaglandins (PGs) as well as the infiltration of inflammatory cells and MPO release in chronic inflammatory response [11,[30][31][32][33]. Furthermore, baicalin inhibited the pro-inflammatory gene expression via down-regulating the TLRs/NF-κB signaling, such as COX-2, iNOS, TNF-α , IL-6, IL-13 and HMBG-1 in cervical tissue and colon tissue [11,30,32]. In addition, baicalin inhibited the production of IL-1β, IL-8, PGE2, leukotriene B4 (LTB4), COX-2, RANKL/OPG ratio, and inhibited the NF-κB, p38 MAPK in many types of cells involved in the process of periodontitis, such as human gingival fibroblasts, periodontal ligament cells, oral keratinocytes and cultured osteoblasts [19,20,[34][35][36].…”
Section: The Pharmacological Effects Of Baicalinmentioning
confidence: 99%
“…The protective effects of baicalin against progression of AD was likely associated with inactivation of the NLRP3 inflammasome and the TLR4/NF‐κB cascade. With respect to baicalin, it should be noted that flavocoxid is prepared from the ethanol extract of roots of Scutellaria baicalensis and Acacia catechu and its major bioactive components include baicalin and catechin . A transgenic mouse model has been developed to assess the neuroprotective effects of flavocoxid in AD.…”
Section: Health Promoting Potentials Of Dietary Phytochemicalsmentioning
confidence: 99%